Kajian Epistemologis terhadap Integrasi Nilai Islam dan Filsafat dalam Proses Pembelajaran di MI PK Al Islam - Triyono, Agus; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study aims to examine the application of integrating Islamic values and philosophy in the learning process at MI PK Al Islam Pucangsawit from the perspective of Islamic epistemology. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings show that knowledge formation in this madrasah relies not only on empirical and rational aspects but also integrates sources of revelation, reason, experience, and intuition in accordance with the principles of Islamic epistemology. Teachers play a central role as educators of values and meaning, supported by a madrasah environment that shapes students’ spiritual character. Knowledge is taught not in a secular or value-free manner but is integrated with the principles of tauhid, morality, and life’s meaning. These findings indicate that the Islamic epistemology approach can create holistic and meaningful learning at the elementary level. This study underscores the importance of integrative and philosophical Islamic education as an effort to restore the true meaning of knowledge in shaping the insan kamil.